Chronic Expanding Hematoma 70 Years After Silicone Gel Breast Augmentation Managed by Arterial Embolization - Daiki Tanaka, MD; Naoki Inafuku, MD; Akane Satake, MD; Fudzuki Hatta, MD; Toshiaki Numajiri, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. We report the case of an 88-year-old woman with a history of breast augmentation approximately 70 years ago, who presented with a 10-cm subcutaneous mass in the lower left breast. The patient, who was noncommunicative and bedridden due to severe dementia, was initially referred for suspected breast cancer. Core needle biopsy and ultrasound findings suggested chronic expanding hematoma (CEH). Given the high invasiveness of complete excision, she was placed under observation. However, 7 months later, the mass was gradually enlarging and rupturing the skin with bleeding, which led to admission to our hospital again. The patient was diagnosed with anemia progression and was referred to the plastic and reconstructive surgery department for further management. Contrast-enhanced computed tomography confirmed a 16-cm mass beneath the pectoralis major muscle, with calcifications and signs of bleeding extravasation. Due to the risks associated with complete excision, we opted for palliative transcatheter arterial embolization (TAE). The procedure successfully halted anemia progression and managed the acute phase. The patient’s condition stabilized with the treatment, allowing for her return to the care facility. To the best of our knowledge, there are no previous reports of such a late onset of CEH, and this is the first report of effective TAE treatment for CEH after breast augmentation. Given the increasing number of long-term breast implant cases, late complications such as CEH may become more common. TAE offers a minimally invasive alternative for patients unable to undergo complete resection.